Agricultural chemical input risk management practices in the paddy crop subsector: Evidence from Sungai Panjang, Sabak Bernam district, Malaysia - Zainol, Rosmiza Mohd; Rosmi, Mohd Nor Mohd; Ibrahim, Mohamad Syahrul Nizam; Masdor, Noor Azlina (Asian Development Policy Review, 2024)
This study aimed to assess Malaysian farmers’ level of chemical input risk management practices and awareness, focusing on pesticide and fertilizer use. We disseminated a questionnaire to 141 farmers cultivating paddy fields in the Sungai Panjang parcel, Sabak Bernam, Selangor, Malaysia, using random sampling. The respondents’ knowledge and practices on chemical input risk management for the use of pesticides were recorded based on the degree of agreement score. We used descriptive analysis to determine the level of interpretation of the mean score. The findings reveal a commendable level of agricultural chemical risk management practices among respondents, as evidenced by their adherence to safety guidelines and poison labels. The notable weaknesses in farmers’ awareness were identified, such as the continued use of unregistered and illegal pesticides, and a lack of emphasis on the effective utilization of personal protective equipment. Embracing sustainable alternatives like green fertilizers and leveraging emerging technologies such as nanotechnology holds promise for enhancing productivity while mitigating environmental impact. Policy initiatives should prioritize incentivizing the adoption of such practices through supportive frameworks and targeted capacity-building efforts. These efforts align with broader sustainable development goals and contribute to the creation of a cleaner food chain and enhanced productivity. To fill these gaps, it is necessary to implement specific intervention programmes that focus on educating and empowering farmers regarding regulatory compliance and safety standards in order to guarantee the safety and quality of domestically produced rice.